2021
DOI: 10.1158/1940-6207.capr-20-0348
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Differences in Juvenile Polyposis Syndrome With or Without a Disease-causing SMAD4/BMPR1A Variant

Abstract: Juvenile polyposis syndrome (JPS) is a clinically diagnosed hamartomatous polyposis syndrome that increases the risk of gastrointestinal cancer. Approximately 40%–50% of JPS is caused by a germline disease-causing variant (DCV) in the SMAD4 or BMPR1A genes. The aim of this study was to characterize the phenotype of DCV-negative JPS and compare it with DCV-positive JPS. Herein, we analyzed a cohort of 145 individuals with JPS from nine institutions, including both pediatric and adult centers. Data analyzed incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…Individuals with gastric polyposis, usually in association with pathogenic variants in SMAD4 are also at risk for gastric cancer, with the lifetime risk estimated to be at least 30% and median age of diagnosis is 58 years ; this has not been reported in association with BMPR1A pathogenic variants. 67,87–91 Estimates of gastrointestinal cancer risk range from 11% 68 to 55%, 89 but none of the studies are prospective long-term studies (which would lead to underestimates), and all are prone to referral-based ascertainment bias (overestimates).
Question: At what age should colonoscopic and upper endoscopic surveillance begin in individuals identified with juvenile polyposis syndrome? Recommendation: We suggest initiating colonoscopic and upper endoscopic surveillance at age 12–15 years, or earlier if symptomatic. Surveillance should be repeated every 1–3 years depending on polyp burden.
…”
Section: Juvenile Polyposis Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with gastric polyposis, usually in association with pathogenic variants in SMAD4 are also at risk for gastric cancer, with the lifetime risk estimated to be at least 30% and median age of diagnosis is 58 years ; this has not been reported in association with BMPR1A pathogenic variants. 67,87–91 Estimates of gastrointestinal cancer risk range from 11% 68 to 55%, 89 but none of the studies are prospective long-term studies (which would lead to underestimates), and all are prone to referral-based ascertainment bias (overestimates).
Question: At what age should colonoscopic and upper endoscopic surveillance begin in individuals identified with juvenile polyposis syndrome? Recommendation: We suggest initiating colonoscopic and upper endoscopic surveillance at age 12–15 years, or earlier if symptomatic. Surveillance should be repeated every 1–3 years depending on polyp burden.
…”
Section: Juvenile Polyposis Syndromementioning
confidence: 99%
“…Individuals with gastric polyposis, usually in association with pathogenic variants in SMAD4 are also at risk for gastric cancer, with the lifetime risk estimated to be at least 30% and median age of diagnosis is 58 years; this has not been reported in association with BMPR1A pathogenic variants. 67,[87][88][89][90][91] Estimates of gastrointestinal cancer risk range from 11% 68 to 55%, 89 but none of the studies are prospective long-term studies (which would lead to underestimates), and all are prone to referral-based ascertainment bias (overestimates).…”
Section: Gastrointestinal Polyposis and Cancermentioning
confidence: 99%
“… 99 There are other further phenotypic differences in JPS between individuals with either a SMAD4 or BMPR1A PV, and those without an identified molecular explanation. 97 , 100 …”
Section: Introductionmentioning
confidence: 99%
“… 105 The number of gastric juvenile polyps can vary, ranging between a few (1–4 polyps), multiple (5–99 polyps) or massive (>100 polyps) – with “few” being most common in patients with BMPR1A PV and “multiple” in SMAD4 PV. 103 Gastrectomy may be required in a subset of JPS to due to the enormous polyp burden or cancer, 100 , 106 and there are reports of individuals with SMAD4 -related JPS presenting with massive gastric polyposis with obstructive symptoms and hypergastrinemia. 103 , 107 Further, SMAD4 PV have been identified in some cases of Ménétrier disease, which is characterized by hypertrophic gastropathy resulting in giant mucosal folds in the proximal part of the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that phenotypic differences exist between individuals with and without a germline variant in BMPR1A or SMAD4 . For patients without a germline variant, this includes a younger age at presentation, polyps predominantly in the lower gastrointestinal tract, and lower risk of requiring colectomy or gastrectomy (5). It is likely that with time, additional genetic changes related to JPS predisposition will be discovered.…”
mentioning
confidence: 99%